Evaluation of the Welsh Government’s Child Rights Impact Assessment procedure under the Children’s Rights Scheme pursuant to the Rights of Children and Young Persons (Wales) Measure 2011 - Simon Hoffman (2015)
Report evaluating the Welsh Government’s Child Rights Impact Assessment procedure under the Children’s Rights Scheme pursuant to the Rights of Children and Young Persons (Wales) Measure 2011. Includes review of principles of CRIA procedure, and recommendations for improvement.